IPO in Russia. The challenges and impact of Section 404 of the Sarbanes-Oxley Act on the post IPO management for public Russian companies - Kosulnikova, Regina (2005)
Recently, initial public offering on the American stock exchanges is one of the preferable ways to increase substantially the capital to support firm's investment projects or repay debt for the Russian private companies. Having become public, the company should consider different aspects of its new status. Apart from straining significant efforts for continuous improvement of company's control and financial reporting systems due to keep credibility and investors' confidence, management must acknowledge its obligation to comply with the American laws and regulations as well as the Security and Exchange Commission (SEC) requirements.